Dissecting spontaneous cerebrospinal fluid collection. (April 2018) - Champagne, Pierre-Olivier; Decarie, Jean-Claude; Crevier, Louis; Weil, Alexander G.
Abstract: Hydrocephalus is a common condition in the pediatric population known to have many causes and presentation patterns. We report from the analysis of 2 cases the existence of a new complication of pediatric hydrocephalus. Naming this entity "dissecting intraparenchymal cerebrospinal fluid collection", we advance a hypothesis regarding its pathophysiology and discuss its clinical implications and management.